De novo assembly of the cattle reference genome with single-molecule sequencing. Issue 3 (19th March 2020) - Rosen, Benjamin D; Bickhart, Derek M; Schnabel, Robert D; Koren, Sergey; Elsik, Christine G; Tseng, Elizabeth; Rowan, Troy N; Low, Wai Y; Zimin, Aleksey; Couldrey, Christine; Hall, Richard; Li, Wenli; et al.
Abstract: Background: Major advances in selection progress for cattle have been made following the introduction of genomic tools over the past 10–12 years. These tools depend upon the Bos taurus reference genome (UMD3.1.1), which was created using now-outdated technologies and is hindered by a variety of deficiencies and inaccuracies. Results: We present the new reference genome for cattle, ARS-UCD1.2, based on the same animal as the original to facilitate transfer and interpretation of results obtained from the earlier version, but applying a combination of modern technologies in a de novo assembly to increase continuity, accuracy, and completeness. The assembly includes 2.7 Gb and is >250× more continuous than the original assembly, with contig N50 >25 Mb and L50 of 32. We also greatly expanded supporting RNA-based data for annotation that identifies 30, 396 total genes (21, 039 protein coding). The new reference assembly is accessible in annotated form for public use. Conclusions: We demonstrate that improved continuity of assembled sequence warrants the adoption of ARS-UCD1.2 as the new cattle reference genome and that increased assembly accuracy will benefit future research on this species.